Tool Usability Parameter in Determining The Performance of Software Testing Tool - Arini, Arini (IJTB (International Journal of Technology And Business), 2019)
Testing is the essential process to make sure and guarantee the functionality and quality of a software based on several parameters and metrics. There are many kinds of testing, unit testing, functional testing, regression testing, etc. But for functional testing itself, testers have to options, manual testing or automation testing using test scripts, but due to market’s demand for stability and effetivity of software, it is not possible through manual testing, testers prefer to do automation testing. To do automation testing in a software, testers need software testing tool or test automation framework to execute test to make it more effective and fast, there are some parameters that it takes to measure how good a software testing tool compare to another software testing tools. One of the parameters is Tool Usability. In this research paper, authors will discuss and compare software testing tools based on their platforms using Tool Usability Metrics, and decide which the best software testing tool in each platforms based on Tool Usability Metrics.